GHOST TAMER - Lyons, Meredith R. (Ft. Collins, Colorado : CamCat Publishing, LLC, 2023)
Aspiring comedian Raely is the sole survivor of a disastrous train wreck. While faced with the intense grief of losing her best friend, she realizes that someone is following her - and has been following her all her life. Trouble is, no one else can see him. For a ghostly tag-along, Casper's not so bad. He might even be the partner Raely needs to fight the evil spirit hell-bent on destroying her. Raely and her friend must learn why this demonic spirit is haunting Raely and how she can stop him before he destroys her life - and her soul. Which, much to her chagrin, means she needs the help of a psychic (although she's sure they are all charlatans) and must rid herself of the pesky ghost hunter who's interested in exploiting her new abilities.
Includes an excerpt from Bone pendant girls by Terry S. Friedman.
Keywords: Comedians -- Fiction; Young women -- Fiction; Brothers; Twins -- Fiction; Good and evil -- Fiction; Railroad accidents -- Fiction; Demoniac possession -- Fiction; Chicago (Ill.) -- Fiction; Paranormal fiction